(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Ekaterina V. Surovtseva (Moscow, Russian Federation) In the context of extensive correspondence of L.N.Tolstoy and, in particular, epistolary appeals of the writer to the authorities, it is considered L.N.Tolstoy’s appeals to the Minister of internal Affairs P.A. Stolypin. In total there are 3 letters-declarations and 2 letters-requests. The main point of divergences between L.N. Tolstoy and P.A. Stolypin is in relation to private land ownership. In letters L.N. Tolstoy justifies the banefulness of the land policy by P.A. Stolypin; P.A. Stolypin in response to the letter defends this policy. Key words: epistolary literature, «letter to the tsar», letter-request, letterdeclaration, Russian literature, censorship, literature and power, L.N.Tolstoy, P.A.Stolypin. DOI 10.23683/1995-0640-2019-2-124-129